Application of acoustic droplet vaporization in ultrasound therapy - Zhou, Yufeng (2018)
Microbubbles have been used widely both in the ultrasonic diagnosis to enhance the contrast of vasculature and in ultrasound therapy to increase the bioeffects induced by bubble cavitation. However, due to their large size, the lifetime of microbubbles in the circulation system is on the order of minutes, and they cannot penetrate through the endothelial gap to enter the tumor. In an acoustic field, liquefied gas nanoparticles may be able to change the state and become the gas form in a few cycles of exposure without significant heating effects. Such a phenomenon is called as acoustic droplet vaporization (ADV). This review is intended to introduce the emerging application of ADV. The physics and the theoretical model behind it are introduced for further understanding of the mechanisms. Current manufacturing approaches are provided, and their differences are compared. Based on the characteristic of phase shift, a variety of therapeutic applications have been carried out both in vitro and in vivo. The latest progress and interesting results of vessel occlusion, thermal ablation using high-intensity focused ultrasound (HIFU), localized drug delivery to the tumor and cerebral tissue through the blood-brain barrier, localized tissue erosion by histotripsy are summarized. ADV may be able to overcome some limitations of microbubble-mediated ultrasound therapy and provide a novel drug and molecular targeting carrier. More investigation will help progress this technology forward for clinical translation.